The Impact of External and Internal Factors on EFL Learners’ Handwriting Legibility The Case of First Year Pupils at Saad Ibn Ouakas Middle School ( Ain el Khadra / M’sila ) - MEBARKI Fahima.BOUAISSI Hakima, Ms. FARRAH Sabah (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
Abstract Algerian middle school learners struggle with handwriting difficulties ,they are striving to overcome this problem, which has a great impact, especially on their academic achievement . This study aims to investigate the effect of external and internal factors on learners' handwriting legibility in their written production. We hypothesized that If the teachers are aware of their pupils’ handwriting difficulties and the factors that impact them they will be able to take action and adapt strategies within the school environment to reduce these problems also understanding the effect of these factors gives teachers a clear insight about handwriting problems and enables them to make the suitable intervention .In order to prove our thesis, a descriptive study was conducted in addition , a qualitative one in order to collect and analyze the data. Thus, to test our thesis, we chose two data collection tools. A questionnaire was designed and delivered online to thirteen middle school English teachers who were randomly selected from different averages, in order to explore their attitudes about their pupils' line and also to take answers for this research. Additionally , A case study was conducted for twenty seven pupils at Saad Ibn Ouakas First Year Middle School in the municipality of Ain el khadra in the state of M’sila, Algeria, in order to verify the various factors affecting the learners' streak during their four normal sessions (lessons) and two exam sessions of 3rd trimester . Based on the results obtained from the two data collection tools used, it can be concluded that the lack of pupils ’ handwriting legibility is due to the impact of both external and internal factors . Furthermore, some recommendations based on the research findings, were proposed at the end of this study in order to enhance learners Handwriting performance .
Keywords: Key words : handwriting , external & internal factors , middle school pupils , handwriting difficulties